OnabotulinumtoxinA (Botox) Nerve Blocks Provide Durable Pain Relief for Men with Chronic Scrotal Pain: A Pilot Open‐Label Trial. (1st December 2014) - Khambati, Aziz; Lau, Susan; Gordon, Allan; Jarvi, Keith A.
Abstract: Introduction: Chronic scrotal pain (CSP) is a common, often debilitating, condition affecting approximately 4.75% of men. While nerve blocks using local anesthetics usually provide temporary pain relief, there are no publications on the use of longer acting nerve blocks to provide more durable pain relief for men with CSP. Aim: The aim of this study was to determine if onabotulinumtoxinA (Botox) cord blocks provide durable pain relief for men with CSP. Methods: In this pilot open‐label study, men with CSP who had failed medical management but experienced temporary pain relief from a standard cord block underwent a cord block with 100U Botox. Main Outcome Measures: The outcomes measured were changes 1, 3, and 6 months post‐Botox injection in (i) a 10‐point visual analog scale (VAS) pain score; (ii) scrotal tenderness on a three‐point scale as rated by physical examination; and (iii) the Chronic Epididymitis Symptom Index (CESI) to measure the severity and impact of scrotal pain on men. Paired t ‐tests were used to compare groups. Results: Eighteen patients with CSP seen between April and September 2013 had Botox injected as a cord block. At the 1‐month follow‐up, pain reduction was reported by 72% of patients (mean VAS score: 7.36 vs. 5.61, P < 0.003), while by physical examination 44 and 34% of the men had either complete or partial resolution of scrotal tenderness. In addition, there was also a significant reduction in CESI scores (22.19 vs. 19.25, P < 0.04). At 3 months, 56% had both sustained pain reduction and reduced tenderness based on the VAS score (mean: 7.36 vs. 6.02, P < 0.05) and physical exam. The CESI score continued to be significantly lower. Unfortunately, by 6 months, most men had a return to their baseline levels of pain and tenderness. Conclusions: Our pilot study found that Botox cord blocks provide pain reduction for 3 months or more for most men with CSP.